Technological Devices: Boon or Bane? - Nor Aine L. Sarip; Melodina L. Dela Cruz (Universal Journal of Educational Research)
The purpose of the study is to determine the relationship between the level of usage to technological devices and the academic performance of Grade II learners in selected Multigrade School in Hilongos South District, Hilongos, Leyte. The study used descriptive survey design since the researcher used checklist to determine the learner’s level of usage to technological devices and survey it used open-ended question to determine how technological devices help the learners in learning. More so, both qualitative and quantitative data were being gathered for the further validation of the quantitative data of the study. The result shows that the level of usage of the learners is at Normal Level. The learners understudy is using technology devices at a tolerable level, that is, 3 – 4 hours in a day. The learners performed well in English with a Closely Approaching Mastery Level in their Quarterly Assessment. The level of usage of the learners to technological devices has a significant relationship with the English performance of the learners. The more exposed the students are to technological devices the more affected their performance in English are. Using to technological devices has a detrimental effect on English performance of the learners. Hence, the parent’s guidance to their children is a must. It can be concluded that usage to technological devices can significantly affect performance. As resulted, using to technological devices has a detrimental effect on English performance. The use of television, cellphones, tablets and computers at a regular basis affects the academic performance of the learners. The more they are using technological devices, the more their academics are negatively affected. Hence, parents or guardian of the learners should be watchful to their children so that they can guide and discipline them in using technological devices to evade bane result from these devices.